Analysis of Cypermethrin and Permethrin in Celery Cabbage by Lanthanum-Modified Activated Alumina QuEChERS Method - Qiao, Fengxia; Lin, Zhiping; Wang, Mengge (Asian Journal of Chemistry, 2014)
A new QuEChERS method based on lanthanum-modified activated alumina for the determination of cypermethrin and permethrin in celery cabbage was proposed. The lanthanum-modified activated alumina that prepared by glycerol complexing-assisted sol gel method using lanthanum as the modifier was employed as the adsorbent of QuEChERS for purification of cypermethrin and permethrin residues in celery cabbage coupled with gas chromatography detection and ethyl acetate as extraction solvent. Factors that affected QuEChERS efficiency were investigated including extraction solvent, extraction time, adsorbent kinds and adsorption time etc. The results showed that this lanthanum-modified activated alumina adsorbent could effectively purify the sample and eliminate the interferences originated from sample matrices. Under the optimized conditions, the fortified recoveries at three spiked levels were ranged from 91.6 to 110 % with RSD £ 4.9 %. Good linearity of the two pesticides was ranged from 0.005 to 1.190 mg/g with r ³ 0.9994.